Small mammal trackways from the Neogene Vinchina Basin, Argentina: Insights into Xenarthra (Dasypodidae), Notoungulata (Typotheria), and Rodentia (Caviomorpha) - De La Fuente, Juan M.; Vera, Rocío B.; Farina, Martín E.; Krapovickas, Verónica (Journal of South American Earth Sciences, 2025)
Neogene deposits of northwestern Argentina host an outstanding ichnological record of the Cenozoic vertebrate faunas developed within a context of continental isolation in South America. The Vinchina (Middle to Late Miocene) and Toro Negro (Late Miocene to Early Pleistocene) formations, at La Rioja Province, have enhanced our understanding of these faunas for over the last 15 years. This contribution aims to explore and report the diversity of trackmakers responsible for five small mammal trackways. Four ichnospecies have been identified, of which three are new. Pichipoda igen. nov. has didactyl to monodactyl manus and tridactyl mesaxonic pes impressions with robust digits with blunt tips. Pichipoda manganae igen. nov. isp. nov. has didactyl manus and is the largest ichnospecies and Pichipoda vizcainoi igen. nov. isp. nov. has almost monodactyl manus impressions. They are interpreted as produced by armadillos (Xenartha: Dasypodidae), specifically P. vizcainoi most likely by tolypeutines (Tolypeutinae), with a trunk length of 21–23.5 cm, and an inferred body mass of 14.7 kg and 8.64 kg, respectively. Fossil armadillo footprints were unknown until now. Tridactylonicha marsicanae igen. nov. isp. nov., has tridactyl to didactyl paraxonic manus and tridactyl mesaxonic pes impression with long, slender, and pointed tips, they are interpreted as produced by hegetotheriids (Notoungulata: Typotheria: Hegetotheriidae) with a body mass of 3.7 kg, and a trunk length of 14 cm. Finally, it is recognized an extensive and complete trackway assigned to Dolichotichnus marae, with tetradactyl paraxonic manus and tridactyl mesaxonic pes impressions, representing an animal of 10.3 kg and a trunk length of 15 cm, is most likely produced by dolichotines (Rodentia: Caviomorpha: Caviidae). These findings provide new records of footprints previously unknown of small mammals, complementing our knowledge of the anatomical traits of small xenarthrans and some of the smallest extinct native ungulates.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Armadillos; Fossil footprints; Mammalian faunas; Miocene; Rodents; South American native ungulates